Flipbook Media Increases Elementary School Students' Interest and Learning Outcomes in Citizenship Education - Insani, Safa Aulia; Ika Ratnaningrum (LPPM Undiksha, 2024)
Students' low interest and learning outcomes are due to the application of less creative and innovative learning media in class III. This research aims to analyze the application of flipbook-based learning media to increase student interest and learning outcomes in Citizenship Education subjects. This research is included in quantitative research. The research method used in this quantitative research design is the ex post facto method. The population in this study was all 30 grade III elementary school students. The sampling technique used by researchers is purposive sampling with a sample size of 30 students. The methods used to collect data are observation, interviews, questionnaires, and tests. The research instruments used in this research were interviews, questionnaires, documentation, and test questions. The data analysis technique used in this research uses the Statistical Package for Social Science (SPSS) computer software application. The research results, namely the correlation results, show that the flipbook learning media and interest in learning have a moderate relationship. The correlation results also show that the flipbook learning media and learning outcomes are closely related. The t-test results showed an increase in the application of flipbook learning media to increase interest in learning for 3rd grade elementary school students. The test results also show an increase in the application of flipbook learning media to improve student learning outcomes. It was concluded that applying flipbook learning media could increase student interest and learning outcomes.